2018
DOI: 10.1159/000486419
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis of Outcome of Patients with Metastatic Leiomyosarcoma in a Tertiary Referral Center

Abstract: Background: Leiomyosarcoma is a common subtype of soft tissue sarcoma originating from smooth muscle. We evaluated the clinical course and treatment outcome of patients with metastatic leiomyosarcoma. Methods: We retrospectively reviewed the records of patients at the University Hospitals Leuven. Results: We identified 122 patients with metastatic leiomyosarcoma, 77 female, median age 59.5 years. Most patients developed leiomyosarcoma in the extremities (35%), the uterus (20%) or the abdomen (19%); 69% develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 24 publications
0
28
0
Order By: Relevance
“…Previous studies have reported no significant differences in the outcomes of patients with advanced or metastatic uterine leiomyosarcoma (uLMS) versus non-uLMS. [28][29][30] Survival of AYAs with metastatic synovial sarcoma was similar to that of adults with synovial sarcoma in the French Sarcoma Group ''METASARC'' observational study (AYAs: 19.5 months vs. adults: 19.7 months). 31 Others have reported a better prognosis for AYAs with metastatic synovial sarcoma compared with that for adults .32,33 Despite similar histological features, characteristic t(X;18) translocation, and fusion transcripts, adults with synovial sarcoma have worse outcomes compared to children with synovial sarcoma.…”
Section: Metastatic Soft Tissue Sarcomas In Ayasmentioning
confidence: 73%
“…Previous studies have reported no significant differences in the outcomes of patients with advanced or metastatic uterine leiomyosarcoma (uLMS) versus non-uLMS. [28][29][30] Survival of AYAs with metastatic synovial sarcoma was similar to that of adults with synovial sarcoma in the French Sarcoma Group ''METASARC'' observational study (AYAs: 19.5 months vs. adults: 19.7 months). 31 Others have reported a better prognosis for AYAs with metastatic synovial sarcoma compared with that for adults .32,33 Despite similar histological features, characteristic t(X;18) translocation, and fusion transcripts, adults with synovial sarcoma have worse outcomes compared to children with synovial sarcoma.…”
Section: Metastatic Soft Tissue Sarcomas In Ayasmentioning
confidence: 73%
“…Harati et al 14 also found that radiation did not significantly improve local recurrence-free survival, disease-specific survival in somatic LMS. However, van Cann et al 32 reported that metastatic LMS patients undergoing radiation treatment had significant better survival compared to patients not undergoing this treatment. Thus, prospective trials are urgently required for further confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Other cancers that metastasise to this organ relatively often are colorectal cancer, melanoma, sarcomas [7]. The prognosis for patients with pancreatic leiomyosarcoma metastasis is unknown, although metastatic sarcoma usually indicates poor prognosis, where the average survival time is between 10-30 months [2]. Metastases can occur as a single neoplastic changes or disseminated lesions.…”
Section: Discussionmentioning
confidence: 99%
“…For primary leiomyosarcoma, the treatment of choice is tumor resection, which can be combined with adjuvant chemotherapy or radiotherapy. About 40% of these cases metastasise, which is associated with poor prognosis [2]. Secondary lesions, usually disseminated, are treated with systemic chemotherapy.…”
Section: Introductionmentioning
confidence: 99%